2003
DOI: 10.1152/ajplung.00170.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous expression of phosphodiesterase 7A in human proinflammatory and immune cells

Abstract: We have determined the expression of phosphodiesterase (PDE) 7A1 and PDE7A2 in human cells that have been implicated in the pathogenesis of chronic obstructive pulmonary disease and asthma. Messenger RNA transcripts were detected by RT-PCR in T lymphocytes, monocytes, neutrophils, airway and vascular smooth muscle cells, lung fibroblasts, epithelial cells, and cardiac myocytes. Human epithelial, T cell, eosinophil, and lung fibroblast cell lines were also positive for PDE7A1 and PDE7A2 mRNA transcripts. By Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 43 publications
(66 reference statements)
2
84
0
1
Order By: Relevance
“…Like PDE4, PDE7, a cAMP-speciic phosphodiesterase, is also highly expressed in human immune system such as thymus, lymph nodes, spleen, and blood leukocytes, suggesting PDE7 as a possible target for treating CNS and airway diseases [22][23][24][25]. A recent study by Cichero et al whereby they applied 3D-QSAR methods for the development of selective PDE 7 inhibitors is worth noting.…”
Section: Pde7 Inhibitorsmentioning
confidence: 99%
“…Like PDE4, PDE7, a cAMP-speciic phosphodiesterase, is also highly expressed in human immune system such as thymus, lymph nodes, spleen, and blood leukocytes, suggesting PDE7 as a possible target for treating CNS and airway diseases [22][23][24][25]. A recent study by Cichero et al whereby they applied 3D-QSAR methods for the development of selective PDE 7 inhibitors is worth noting.…”
Section: Pde7 Inhibitorsmentioning
confidence: 99%
“…6 PDE7A PDE7A, mRNA endotelyal ve immün hücrelerde-ayn1 zamanda insan proinflamatuar hücrelerinde neredeyse her yerde bulunacak şekilde dağılır. 102,103 PDE7A, mRNA tarafından yaygın nöronal ve nö-ronal olmayan hücre populasyonlarında, sıçan beyninde dağılım gösterir. Periferal organlarda, PDE7A mRNA'sının böbrek medulla, testis, karaciğer ve böbrek üstü bezlerinde yüksek seviyede olduğu görülmüştür.…”
Section: Pde7 Ailesiunclassified
“…In a similar fashion, it has been suggested that targeting PDE7 may also be beneficial in view of its widespread distribution in various inflammatory and structural airway cell types implicated in the pathogenesis of COPD [61,62]. However, targeting PDE7 with a chemical inhibitor failed to modify cell function in vitro, but when used in combination appeared to enhance the inhibitory action of a PDE4 selective inhibitor [62].…”
Section: Beyond Roflumilastmentioning
confidence: 99%
“…However, targeting PDE7 with a chemical inhibitor failed to modify cell function in vitro, but when used in combination appeared to enhance the inhibitory action of a PDE4 selective inhibitor [62]. Targeting both PDE4 and PDE7 with antisense oligonucleotides suppressed various indices of airway inflammation in mice exposed to cigarette smoke [20], and whilst combination treatment was not compared with component oligonucleotides against the inflammatory response, it appears that simultaneous targeting of PDE4 and PDE7 provided a greater inhibitory activity than targeting PDE4 only and warrants the development of mixed PDE-inhibitors for the treatment of COPD.…”
Section: Beyond Roflumilastmentioning
confidence: 99%